STUDI ANALISIS KONSEP E-GOVERNMENT: SEBUAH PARADIGMA BARU DALAM PELAYANAN PUBLIK - Bambang Irawan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The main concern of this article is all about e-government concept. Electronic government is at the forefront of government effort to provide information and services to citizens, business, government employees, other governmental units, and third sector organizations. It was expected to improve state capacity by making up for deficiencies in bureaucratic analyses, promoting unbiased treatment in bureaucracy’s dealing with public, ensuring accountability, injecting speed into governmental operations, generating necessary and accurate data, curtailing corruption through proper record keeping.